Energy Recovery And Carbon Dioxide Emission Perspectives Of Anaerobic Digestion Of Palm Oil Mill Effluent - Chou, Kian Weng (2018)
This study aims to evaluate the performance of two-stage anaerobic digestion (AD) of POME with aerobic post-treatment. The single-stage AD served as a comparison for the two-stage AD. Evaluation on the AD was mainly focused on biogas production and treatment efficiency whereas the evaluation on aerobic post-treatment was emphasized on treatment efficiency and final effluent quality. Laboratory scale anaerobic digester was used to develop single-stage AD then modified into a two-stage AD. Laboratory scale bioreactors were used as activated sludge system (AS) then modified into activated sludge system with sludge recirculation (ASR) for aerobic post-treatment.